RNAi-mediated RPL34 knockdown suppresses the growth of human gastric cancer cells - LIU, HUI (Oncol Rep, 2015)
An increasing body of evidence suggests that ribosomal proteins may have ribosome-independent functions and may be involved in various physiological and pathological processes. To examine the role of ribosomal protein L34 (RPL34) in cancer transformation, we assessed its expression in gastric cancer cell lines and found it highly expressed. We further used lentivirus-mediated small interfering RNAs (siRNAs) to knockdown RPL34 expression in the human gastric cancer cell line SGC-7901. RNA interference (RNAi)-mediated inhibition of RPL34 expression in SGC-7901 cells significantly suppressed cell proliferation, increased apoptosis and arrested cells in the S phase. The results of the present study suggest that RPL34 plays a critical role in cell proliferation, cell cycle distribution and apoptosis of human malignant gastric cells.